1995
DOI: 10.1007/bf00932415
|View full text |Cite
|
Sign up to set email alerts
|

Transovarial transmission ofNosema locustae (Microsporida: Nosematidae) in the migratory locustLocusta migratoria migratorioides

Abstract: Nosema locustae, a microsporidian parasite of locusts and grasshoppers, was transovarially transmitted to the progeny of infected Locusta migratoria reared for up to F14 generations. The mortality of infected progeny in each generation was higher than that of uninfected controls and ranged from 67.6% to 95.5%. Infected female survivors transmitted the microsporidium to the progeny via eggs. The developing eggs harboured vegetative stages of N. locustae, and development of the microsporidium occurred during emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 16 publications
1
35
0
1
Order By: Relevance
“…On [17,27] or even found increased production of sexuals in naturally infected colonies [22]. Similarly [28] but so far has not been reported from N. bombi and seems unlikely from detailed investigations of reproductive structures [27]. Within the colony, N. bombi spreads by ingestion of spores shed by infected workers [14].…”
Section: Introductionmentioning
confidence: 98%
“…On [17,27] or even found increased production of sexuals in naturally infected colonies [22]. Similarly [28] but so far has not been reported from N. bombi and seems unlikely from detailed investigations of reproductive structures [27]. Within the colony, N. bombi spreads by ingestion of spores shed by infected workers [14].…”
Section: Introductionmentioning
confidence: 98%
“…However, female host longevity in the flight cage was still independent of the number of microsporidian spores it contained after partitioning out the effect of host size (Spearman rank correlation of female host longevity in the cage versus residuals from the regression of the numbers of spores per female host upon host size: r s = -0.239, n = 11, ns). (Raina et al, 1995). For A scotica too, the fat body appeared to be the only tissue type that was infected with microsporidia, although heavily infected hosts also contained large numbers of spores in their haemocoels, suspended in haemolymph.…”
Section: Resultsmentioning
confidence: 98%
“…Parasites and parasitoids of other hymenopteran species are known to become infected with their hosts' microsporidia (Blunck, 1954;Briano et al, 1996) and may potentially act as conduits for the horizontal transfer of parasites among host species (Werren et al, 1995). That (Raina et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…This is highly relevant for the transmission of the pathogen to the second generation of grasshopper and the long-term management concerns. Although the transmission of microsporidia between hosts occurs horizontally when the spores are ingested, the vertical transmission from parent to progeny via eggs is known to be an important route for many of the insect-infecting microsporidia (e.g., Ewen and Mukerji 1980;Streett et al 1993;Raina et al 1995). In preliminary laboratory examinations we observed that 18-52 % of the offspring from infected O. senegalensis were infected when the parents were infected at late instars (Tounou 2007), which suggests survival and continual impact of P. locustae as a regulating factor of grasshopper populations in this study.…”
Section: Discussionmentioning
confidence: 99%